2010
DOI: 10.1038/nature09172
|View full text |Cite
|
Sign up to set email alerts
|

Convergent evolution of chicken Z and human X chromosomes by expansion and gene acquisition

Abstract: In birds, as in mammals, one pair of chromosomes differs between the sexes. In birds, males are ZZ and females ZW. In mammals, males are XY and females XX. Like the mammalian XY pair, the avian ZW pair is believed to have evolved from autosomes, with most change occurring in the chromosomes found in only one sex – the W and Y chromosomes1–5. By contrast, the sex chromosomes found in both sexes – the Z and X chromosomes – are assumed to have diverged little from their autosomal progenitors2. Here we report find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
224
1
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 225 publications
(235 citation statements)
references
References 39 publications
5
224
1
5
Order By: Relevance
“…The transposable element accumulation in the X-specific region is consistent with the greater quantity of such insertions in other sex chromosomes (X of mammals and Z of chickens) (14), and can be explained by its lower recombination frequency than that of autosomes; this difference arises because recombination occurs in only females, because of lack of recombination between the X-and Y-specific region in males (or HSY in hermaphrodites), in which the X spends one-third of its time. In Silene latifolia, whose sex chromosomes are extremely large and heteromorphic (the Y chromosome is 570 Mb and the X is 420 Mb), these changes have evolved over ∼10 million y (21).…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…The transposable element accumulation in the X-specific region is consistent with the greater quantity of such insertions in other sex chromosomes (X of mammals and Z of chickens) (14), and can be explained by its lower recombination frequency than that of autosomes; this difference arises because recombination occurs in only females, because of lack of recombination between the X-and Y-specific region in males (or HSY in hermaphrodites), in which the X spends one-third of its time. In Silene latifolia, whose sex chromosomes are extremely large and heteromorphic (the Y chromosome is 570 Mb and the X is 420 Mb), these changes have evolved over ∼10 million y (21).…”
Section: Discussionsupporting
confidence: 66%
“…In mammals, the gene order in the X chromosomes has been conserved across such distantly related species as human, cat, horse, cattle, and elephant, with the exception of mouse (22)(23)(24)(25)(26). In the human X and chicken Z, gene trafficking and sequence expansion have been detected, using comparisons with orthologous autosomal segments of other species (12)(13)(14). Given its recent origin, the differences in gene content between papaya and V. monoica are surprising.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Nanda and colleagues recently reported that the Z is highly conserved across at least 14 species representing 11 families (Nanda et al 2008). The Z sex chromosome carries~1000 genes (Bellott et al 2010), most of which are ostensibly unrelated to sex. However, most recently, it has been show that the Chicken Z chromosome, like the mammalian X chromosome, is enriched for testis-expressed genes (Bellott et al 2010).…”
Section: Avian Sex Chromosomesmentioning
confidence: 99%
“…The Z sex chromosome carries~1000 genes (Bellott et al 2010), most of which are ostensibly unrelated to sex. However, most recently, it has been show that the Chicken Z chromosome, like the mammalian X chromosome, is enriched for testis-expressed genes (Bellott et al 2010). One of these is DMRT1 (Doublesex and Mab-3 Related Transcription factor, #1), which has a key role in testis development and may represent the master avian testis determinant (Smith et al 2009a) (described below).…”
Section: Avian Sex Chromosomesmentioning
confidence: 99%